Relationship between geomagnetic storms and occurrence of ionospheric irregularities in the west sector of Africa during the peak of the 24th solar cycle - Ondede, George Ochieng; Rabiu, A. B.; Okoh, Daniel; Baki, Paul; Olwendo, Joseph; Shiokawa, Kazuo; Otsuka, Yuichi (Frontiers in Astronomy and Space Sciences, 2022)
The study of ionospheric irregularities is important since many technological systems rely on the ionosphere. In this work, we use data from Global Navigation Satellite Systems (GNSS) receiver installed in Abuja, Nigeria and the geomagnetic data from the World Data Centre(WDC) in Kyoto, Japan. We use the data to investigate the relationship between geomagnetic storm and ionospheric irregularity occurrences using rate of change of total electron content (TEC) index (ROTI) during the peak of the 24th solar cycle. The occurrences of irregularities were investigated on day to day and on a seasonal basis. The periodogram power spectral density (PSD) computed from ROTI using the MATLAB periodogram function suggested diurnal and seasonal variations. The nighttime ionospheric irregularities, which are attributed to ionospheric plasma irregularities in the equatorial ionospheric F region, were found to be prevalent. To investigate the relationships between strengths of the irregularities and geomagnetic storms, the Disturbance Storm Time (Dst) index was correlated with the ionospheric irregularity parameter, ROTI. The results showed that there was low correlation, cc=0.073017, between the Dst and the ROTI, implying that the strengths of ionospheric irregularities occurring during geomagnetic storms are not strictly decided by the magnitudes of the storms. The geomagnetic storms caused enhanced development or inhibition of ionospheric irregularities. We observed that the bulk of the storms occurring during the period of this study are not associated with ionospheric irregularities. Finally, the investigation showed that the Coronal Mass Ejections (CME)-driven geomagnetic storms, were more compared to the Co-Rotating Interaction Regions (CIR)-driven geomagnetic storms, during the peak of the 24th solar cycle. The results of this work confirm the findings by other researchers.